Odpowiedź :
x=(√(4+√7) +√(4-√7) )^2
x=[√(4+√7)]² + 2*[√(4+√7)*√(4-√7)] + [√(4-√7)]²
x=4 + √7 + 2[√(16-7)] + 4 - √7
x=4 + 4 + 2√9 = 16 + 2*3= 16+6= 22
x=[√(4+√7)]² + 2*[√(4+√7)*√(4-√7)] + [√(4-√7)]²
x=4 + √7 + 2[√(16-7)] + 4 - √7
x=4 + 4 + 2√9 = 16 + 2*3= 16+6= 22
dla ułatwienia obliczeń oznacz
a = 4 + √ 7
b = 4 - √ 7
x = ( √a + √b )² = (√a)² + 2 √a √b +(√b)² = a + 2 √ab + b =
= 4 + √ 7 + 2√ z (4 + √ 7 )(4 - √ 7 ) + 4 - √ 7 = 8 + 2 √ z 16 - 7 =
8 + 2 √ 9 = 8 + 6 = 14
x = 14
a = 4 + √ 7
b = 4 - √ 7
x = ( √a + √b )² = (√a)² + 2 √a √b +(√b)² = a + 2 √ab + b =
= 4 + √ 7 + 2√ z (4 + √ 7 )(4 - √ 7 ) + 4 - √ 7 = 8 + 2 √ z 16 - 7 =
8 + 2 √ 9 = 8 + 6 = 14
x = 14